EFFECT OF BRUTO REGIONAL DOMESTIC PRODUCTS AND REGIONAL EXPENDITURE AGAINST POVERTY IN DISTRICT / NORTH SUMATERA CITY 2014-2016 - Winda Suheini Zahwa Ritonga; Asnawi Asnawi (Journal of Malikussaleh Public Economics, 2018)
The purpose of this study is to determine the effect of Gross Regional Domestic Products(GRDP) and Government Expenditure on Poverty in the District / City of North Sumatra in 2014-2016. This study uses a panel data obtained from the Central Bureau of Statistics. The data analysis method used in this study is a panel data regression analysis method with Random Effect Model. The results show that GRDP has a positive influence on poverty, while Government Expenditures  do not affect poverty.